Investigating Bodily Injury - Nyitrai, Endre; Girhiny, Kornel; Boi, Laszlo; Halasz, Henrietta Farkasne; Haspel, Orsolya (European Scientific Journal, ESJ, 2022)
This study shall analyse the statutory provisions on bodily injuries or batteries with a special outlook to the difficulties caused by the pandemic. The study shall introduce the relations of corona virus and HIV virus to bodily injuries. Interpretation of the recommendations of criminalistics is indispensable for the detection of bodily injuries, similarly, the identification of the methods revealing criminal actions and the questions to be asked during the interrogation of the suspect are also absolute necessities in the process.